Childhood Mesenteric Adenitis -The Spectrum of Findings - Shrestha, A. L.; Adhikari, G. (Kathmandu University Medical Journal, 2021)
Background Mesenteric adenitis in children (≤ 18 years) can present with varied findings often causing a diagnostic confusion. In children, considering the inadequacies in history and physical examination, an accurate clinic-radiological diagnosis backed up with laboratory data as indicated becomes important to avoid misdiagnosis and futile interventions. Objective To study the profile of children evaluated for acute abdominal pain and diagnosed as mesenteric adenitis. Method A retrospective review of children with abdominal symptoms, diagnosed to have mesenteric adenitis between January 2018 and December 2020. Result A total of 85 patients (63 males, 22 females) were identified presenting at mean age of 6 years (range 4 months-16 years). Primary Mesenteric Adenitis (PA) was found in 62, Secondary Mesenteric Adenitis (SA) in 11 and Complicated Primary Mesenteric Adenitis (CPA) was identified in 12. All with PA responded well to supportive care. Those with SA were treated for the primary cause and the ones with Complicated Primary Mesenteric Adenitis were managed by treating the complication. All had a favorable outcome. Conclusion When managing a child with abdominal pain, mesenteric adenitis should be considered. Once clinically suspected, tailored management approach results in fruitful outcome.